Pelatihan Pengelolaan Pembelajaran Online Learning Management System Menggunakan Moodle - Dian Rahadian; Iman Nasrulloh; Siti Husnul Bariah; Kuntum An Nisa Imania; Yuniar Purwanti; Dudi Suprihadi; Fikri Azis Athoillah (Lembaga Pengabdian kepada Masyarakat Institut Pendidikan Indonesia Garut, 2020)
The impact of the Covid 19 pandemic requires teachers to change the learning approach, which was originally carried out face-to-face at school to distance learning using internet technology. Teachers have a strategic role and function in learning, of course, the quality of a teacher is the main key to managing learning. This training aims to equip teachers in managing the online learning management system using Moodle so that learning components can be integrated into one learning service and are expected to be implemented in the implementation of learning. This activity is a training part of the community service program carried out by the lecturers of the Information Technology Education Study Program. The activity is carried out by presenting material about online learning management and direct practice of managing online-based content / subject matter. Based on the results of filling out a questionnaire from 14 teacher participants, they responded positively to the online learning management training.